ANALISIS KEAMANAN LALU LINTAS WEB PADA PERANGKAT IOT ESP8266 MENGGUNAKAN TEKNIK SNIFFING PAKET - Pariyasto, Sofyan; Agus, Raja Tama Andri; Priyulida, Fitria; Julita, Rina (Smart Education, 2025)
Abstract: Technological developments in recent years have increased quite rapidly, especially in the field of IoT (Internet of Things). With the increasing development of IoT, of course, in line with the increasing use of IoT devices in everyday life. With the increasing number of IoT devices, the issue of data security in IoT devices is certainly one of the important things that must be considered. In this study, a security analysis of web data traffic was conducted on the IoT NodeMCU esp8266 device. The experiment was conducted using two IoT devices acting as senders and receivers of data and one computer device as an attacker. In the analysis process, three scenarios were carried out: sending data without encryption, sending data with base64 encryption without a key, and finally sending data with XOR encryption with a key inserted in the header of the sent data packet. The tapping process was carried out using Wireshark software. From the results of the trials carried out, the entire data transfer process between the two IoT devices can be fully intercepted by Wireshark. Plaintext data (without encoding) tends to be easier to obtain information, while data with encryption without a key on base64 must be analyzed for its pattern to be able to be decrypted. And for encryption that requires a key in XOR, further analysis is carried out by looking for the key inserted in the header so that decryption can be carried out. Keywords: Internet Of Things (IOT); Wireshark; NodeMCU; Base64 Encoding, XOR Encoding. Abstrak: Perkembangan teknologi dalam beberapa tahun terakhir meningkat dengan cukup pesat khususnya dalam bidang IOT (Internet Of Things). Dengan semakin meningkatnya perkembangan IOT tentu sejalan dengan meningkatnya penggunaan perangkat IOT dikehidupan sehari-hari. Dengan semakin banyaknya perangkat IOT yang ada tentu masalah keamanan data dalam perangkat IOT menjadi salah satu hal penting yang harus diperhatikan. Dalam penelitian ini dilakukan analisa keamanan lalu lintas data web pada perangkat IOT NodeMCU esp8266. Percobaan dilakukan dengan menggunakan 2 perangkt IOT yang bertindak sebagai pengirim dan penerima data dan satu perangkat komputer sebagai penyerang. Dalam proses analisa dilakukan tiga skenario yaitu pengiriman data tanpa enkripsi, pengiriman data dengan enkripsi base64 tanpa key, dan yang terakhir pengirimn data dengan enkripsi XOR dengan key disisipkan di header paket data yang dikirim. Proses penyadapan dilakukan dengan menggunakan perangkat lunak Wireshark. Dari hasil ujicoba yang dilakukan seluruh proses transfer data antara kedua perangkat IOT dapat disadap sepenuhnya oleh Wireshark. Data plaintext (tanpa encoding) cenderung lebih mudah didapatkan informasinya, sementara data dengan enkripsi tanpa key pada base64 harus dianalisa polanya untuk bisa dilakukan dekripsi. Dan untuk enkripsi yang membutuhkan key pada XOR dilakukan analisa lanjutan dengan mencari key yang disisipkan diheader agar bisa lakukan dekripsi. Kata kunci: Internet Of Things (IOT); Wireshark; NodeMCU; Base64 Encoding, XOR Encoding.